PENGARUH PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD PADA PENGADAAN BARANG DAN JASA - Nur Ainun, Mia; Castellani, Justinia (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2024)
This research aims to determine the effect of implementing Internal Control on Fraud Prevention in the Procurement of Goods and Services at Telkom Corporate University, which is one of the Units at PT Telkom Indonesia. This Research was conducted on 60 people implementing goods and services procurement activities at Telkom Corporate University. The research was carried out using quantitative methods with a descriptive and verification approach using survey methods. Research data from the results of distributing questionnaires is in the form of ordinal data which is then transformed into interval data using the Method of Successive Interval (MSI). The analysis technique used in this research by verification analysis in the form of correlation coefficient analysis, simple liner regression test, coefficient of determination analysis and hypothesis test (t- test). The results of the research show that the implementation of Internal Control positive and significant has effect on Fraud Prevention in the Procurement of Goods and Services at Telkom Corporate University by 43.6% and 56,3% by other factors.